2020
DOI: 10.1007/s00464-019-07364-y
|View full text |Cite
|
Sign up to set email alerts
|

Transpancreatic biliary sphincterotomy for biliary access is safe also on a long-term scale

Abstract: Background Transpancreatic biliary sphincterotomy (TPBS) is an advanced cannulation method for accessing common bile duct (CBD) in endoscopic retrograde cholangiopancreatography (ERCP). If CBD cannulation is difficult, an endoscopist can open the septum between the pancreatic and biliary duct with a sphincterotome to gain access. Long-term results of this procedure are unclear. We wanted to evaluate the short-and long-term complications of TPBS on patients with native papilla and benign indication for ERCP. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Concerns related to long-term complications of TPBS have been expressed [22,34]. A recent retrospective casecontrol study from Helsinki found similar long-term complication rates between the TPBS group and a control group in which only biliary sphincterotomy was performed [35]. We plan to perform a follow-up study of the present multicenter trial in order to assess the long-term adverse events associated with TPBS.…”
Section: Discussionmentioning
confidence: 95%
“…Concerns related to long-term complications of TPBS have been expressed [22,34]. A recent retrospective casecontrol study from Helsinki found similar long-term complication rates between the TPBS group and a control group in which only biliary sphincterotomy was performed [35]. We plan to perform a follow-up study of the present multicenter trial in order to assess the long-term adverse events associated with TPBS.…”
Section: Discussionmentioning
confidence: 95%
“…Theoretical concerns of TPS-related long-term consequences like PD stenosis [54] have not been confirmed in one prospective study [52]; however, studies comprising follow-up beyond 1 year have been stipulated [55]. In 2020, 2 retrospective single-center studies from Finland (n = 143) [56] and from the Stanford University (n = 369) [57] found TPS to be safe even on a long-term scale [56]. Compared to needle-knife precut, a 2017 meta-analysis [32] showed significantly higher biliary cannulation rates and less bleeding complications for TPS, while PEP risk was not significantly different.…”
Section: Transpancreatic Sphincterotomymentioning
confidence: 99%
“…Furthermore, a prospective randomized multicenter study published in 2021 compared TPS and DGW and found no difference in PEP-risk but a superior biliary cannulation rate for TPS (84.6% vs. 69.7%) [68]. Promoting TPS as an advanced technique early in the course of DBC [50,56,57] is also supported by the meta-analysis data displaying a higher cannulation success and lower bleeding rate for TPS even when compared to the long-time standard NKPP [32]. In situations with DBC as defined by the ESGE "5-5-2 criteria" [1], a recent study labeled TPS an "effective advanced cannulation method with an acceptable complication rate" [8].…”
Section: Modified Esge Algorithm For Biliary Cannulationmentioning
confidence: 99%
“…In our recent case-control study, 143 TPBS patients and 140 control patients were followed for 4-10 years after index ERCP. No difference in long-term complications occurred between the groups [4]. Sundaram and Jagtap, as well as guidelines from the European Society of Gastrointestinal Endoscopy [3], suggest that in difficult cannulation situations, a prophylactic pancreatic stent should be placed and rectal nonsteroidal anti-in-flammatory drugs (NSAIDs) administered to prevent PEP.…”
Section: Reply To Sundaram and Jagtapmentioning
confidence: 99%